Organizational Commitment Existence Achievement on MAN 2 Padangsidimpuan Teacher Performance - Surbakti, Raisah; ., Zulhimma (KnE Social Sciences, 2023)
Organizational commitment is one important factor in the sustainability of an organization. The formulation of the problem raised in this study is how the existence of organizational commitment, and how the influence of organizational commitment on teacher performance in Madrasah Aliyah Negeri 2 Padangsidimpuan, the purpose of this study is to find the existence of Organizational Commitment and the effect of organizational commitment on teacher performance in Madrasah Aliyah Negeri 2 Padangsidimpuan. This research was conducted at Madrasah Aliyah Negeri 2 Padangsidimpuan, Padangsidimpuan City, North Sumatra Province, Indonesia. This research was conducted in April - June 2019. The research method used was a survey method with a questionnaire instrument. The population of all MAN 2 Padangsidimpuan teachers. The sample used by the census technique is the total population, which amounts to 76 respondents, data analysis techniques: validity test, reliability test, hypothesis test. The analysis technique is a simple linear regression analysis. The results of the study are: The organizational commitment of MAN 2 Padangsidimpuan tends to be in the moderate category at 48.1 percent and 51.9 percent is another influence. Organizational Commitment consisting of affective commitment, continuance commitment, and normative commitment has a strong positive influence on the performance of MAN 2 Padangsidimpuan teachers. Keywords: Organizational commitment; sustainability; performance